Improving Employee Performance by Strengthening Teamwork, Motivation and Increasing Job Satisfaction in Business Engaged in Health Service Sector - Putri, Intan Irani; Reniati*, Reniati; Wibawa, Dian Prihardini (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
The purpose of this study was to analyze and determine the effect of teamwork, motivation and job satisfaction on employee performance. This research is a type of descriptive and quantitative research with a total sample of 37 respondents. The sampling technique in this study used the census or saturation method. The analytical method used is multiple linear regression analysis. The results of this study indicate that teamwork, motivation and job satisfaction partially have a positive and significant effect on employee performance. Simultaneous test results show that teamwork, motivation and job satisfaction have a positive and significant effect on employee performance. The implication will be optimal if the work team is solid, motivation is high and job satisfaction increases. Keywords: Cooperation; Motivation; Job satisfaction; Employee Performance; Health Service Sector